البيئة والتحول نحو الاستدامة: نظرة إسلامية - عودة الجيوسي (International Institute of Islamic Thought, 2013)
يهدف هذا البحث إلى إلقاء الضوء على التصور الإسلامي لفكرة التنمية الإسلامية، ونقد الفكر الغربي وما يعانيه من إشكالية أدت إلى تدهور نظام البيئة، وتلوّث الهواء، وتردي حالة الحياة الإنسانية، المتمثّلة في الفقر والمرض والجوع، وصولاً إلى تبيان مدى الخلل الحاصل في الأنظمة البيئية نتيجة نسق التفكير الغربي، ونمط التنمية الغربية اللذين يعتمدان مبدأ النمو لأجل النمو، وتشجيع الاستهلاك، وحتى ربطه بمفهوم السعادة. يهدف البحث كذلك إلى طرح رؤية جديدة للتنمية المستدامة (الطيبة)، مستمدةً من الفكر الإسلامي الذي يعتمد مبادئ العدل، والإحسان، وصلة الرحم، والحد من الفساد. This article intends to shed some light on the Islamic worldview of sustainable development. It also aims to critique the underpinnings of the western model of development which led to ecological degradation, poverty, pollution, waste and new types of chronic diseases. It highlights the pitfalls of the notion of "growth for the sake of growth" which has resulted in a misuse and overconsumption of resources. The paper also presents a proposed conceptual framework that is based on justice (adl); beauty (ihsan); protection of social and human capital (arham) and control of corruption (fassad).